Paket Wavelet Coifman Biorthogonal (PWCB) untuk Kompressi Citra Diam : Perbandingan dengan Paket Wavelet Coifman Orthogonal (PWCO) - Hasiholan Sianipar & Sjamsjiar Rachman, Rismon (Institute of Research and Community Outreach, 2002)
Digitized images have replaced analog images as photographs or x-rays in many different fields. In their raw form, digital images require a tremendous memory capacity for storage and large amount of bandwidth for transmission. In the last two decades, many researchers have been devoted to develop new techniques for image compression. More recently, wavelets have become a cutting edge technology for compressing the images by extracting only the visible elements. In this paper a biorthogonal Coifman wavelet packet based image decomposition algorithm has been implemented. Also, a nonuniform threshold technique based on average intensity values of pixels in each sub-band has been proposed to remove the insignificant wavelet coefficients in the transformed image. Experimental results are obtained to compare the BCoif2, BCoif3 and BCoif4 compactly supported (Coifman) biorthogonal wavelets on various test images using two important performance parameters -compression ratio (CR) and PSNR. The result showed that PSNR of PWCB is greater than PWCO. Abstract in Bahasa Indonesia : Citra digital telah lama menggeser peran citra analog seperti citra foto atau citra sinar x. Dalam bentuk asli, citra memerlukan kapasitas memori yang sangat besar untuk penyimpanan dan lebar-bidang yang besar untuk transmisi. Dalam dua dekade terakhir, sejumlah peneliti telah mengembangkan teknik-teknik kompressi mutakhir. Wavelet telah menjadi teknologi acuan untuk kompressi citra. Pada paper ini, algoritma dekomposisi citra berbasis paket wavelet Coifman biorthogonal telah diimplementasikan termasuk teknik thresholding tidak seragam berbasis intesitas piksel dalam sub-bidang citra. Hasil percobaan diperoleh untuk membandingkan wavelet-wavelet biorthogonal Bcoif2, Bcoif3, dan Bcoif4 atas beberapa citra uji menggunakan parameter rasio kompressi (CR) dan PSNR. Hasil perbandingan menunjukkan bahwa PSNR dari PWCB lebih besar dari PWCO. Kata kunci : paket wavelet, kompresi citra, PWCB, PWCO.